2014
DOI: 10.1590/1413-812320141911.46062013
|View full text |Cite
|
Sign up to set email alerts
|

Estigma social e as famílias de doentes com tuberculose: um estudo a partir das análises de agrupamento e de correspondência múltipla

Abstract: Estigma social e as famílias de doentes com tuberculose: um estudo a partir das análises de agrupamento e de correspondência múltipla Social stigma and the families of patients with tuberculosis: a study based on cluster and multiple correspondence analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
0
11
0
8
Order By: Relevance
“…The multiple correspondence analysis (MCA) is introduced here, which is a data-driven method which can be used to identify non-linear interactions in categorical data. Although MCA has been successfully implemented in different disciplines including psychology and health sciences (Bouilland and Loslever, 1998; Guinot et al, 2002; Meyer et al, 2004; Ambrogi et al, 2005; Almeida et al, 2009; Rennie and Roberts, 2009; Pinti et al, 2010; Avolio et al, 2013; Costa et al, 2013; Sagawa et al, 2013; Ayele et al, 2014; Touso et al, 2014), it is seldom encountered in neuroimaging literature. This method was applied here to study the functional connectivity of BG, centers which have shown multiple non-linear interactions in both animal and human studies (Rodriguez et al, 2003a,b; Marceglia et al, 2006; Schroll and Hamker, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The multiple correspondence analysis (MCA) is introduced here, which is a data-driven method which can be used to identify non-linear interactions in categorical data. Although MCA has been successfully implemented in different disciplines including psychology and health sciences (Bouilland and Loslever, 1998; Guinot et al, 2002; Meyer et al, 2004; Ambrogi et al, 2005; Almeida et al, 2009; Rennie and Roberts, 2009; Pinti et al, 2010; Avolio et al, 2013; Costa et al, 2013; Sagawa et al, 2013; Ayele et al, 2014; Touso et al, 2014), it is seldom encountered in neuroimaging literature. This method was applied here to study the functional connectivity of BG, centers which have shown multiple non-linear interactions in both animal and human studies (Rodriguez et al, 2003a,b; Marceglia et al, 2006; Schroll and Hamker, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The search for these areas confirms a remarkable centrality in health services, similarly to what is observed in education, culture, leisure, and job offers in these urban centers. [44][45] Regarding pulmonary TB diagnosis in patients coinfected by HIV, the proportion of sputum smear microscopy was high but the proportion of bacteriological confirmation was low in the group with satisfactory quality. These results may reflect operational barriers for the execution of diagnostic tests in health services, for instance low quality of sputum collection, resulting from inadequate guidance on the procedure, inadequate storage and transportation of samples, coinfection by HIV, which hinders the test reading, and flaws in the structure of the laboratories and during information exchange with health services.…”
Section: /16mentioning
confidence: 99%
“…1,5 Adherence to treatment is a multidimensional phenomenon, with several associated factors, such as the conception of the disease, the treatment itself, the relationship between the health system and professionals. 6 It is worth considering that the scientific and cultural conceptions of health professionals do not always come close to those presented by health service users, which influence their behaviors. Each person experiences a particular illness and treatment process, which can be obstacles to the success of treatment and the consequent reduction in the number of cases in the population.…”
Section: Introductionmentioning
confidence: 99%
“…Each person experiences a particular illness and treatment process, which can be obstacles to the success of treatment and the consequent reduction in the number of cases in the population. 6,7 A bibliographic survey was carried out in the Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library Online (SciELO) and in the Online Medical Literature Search and Analysis System (MEDLINE), for the period of 2007 to 2018, aiming to know the qualitative scientific production in health about tuberculosis and the state of the art about the experience of treatment of people with tuberculosis. It was established, as criteria for bibliographic investigation, to be an original article of national and international origin, published in Portuguese, Spanish and/or English that addressed the treatment of tuberculosis from the perspective of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation